Testing the Central Gain Model: Loudness Growth Correlates with Central Auditory Gain Enhancement in a Rodent Model of Hyperacusis. (21st May 2019) - Auerbach, Benjamin D.; Radziwon, Kelly; Salvi, Richard
Graphical abstract: Highlights: Explicit test of the central gain model of hyperacusis using a dual behavioral-electrophysiological approach. Combined stable measure of loudness perception using auditory reaction time with chronic electrophysiological recordings. Examined effect of salicylate on evoked-response in auditory cortex and inferior colliculus of behaviorally phenotyped rats. Salicylate induced parallel changes to loudness and evoked responses consistent with temporary hearing loss and hyperacusis. Behavioral and physiological changes were correlated within an animal, providing strong support for the central gain model. Abstract: The central gain model of hyperacusis proposes that loss of auditory input can result in maladaptive neuronal gain increases in the central auditory system, leading to the over-amplification of sound-evoked activity and excessive loudness perception. Despite the attractiveness of this model, and supporting evidence for it, a critical test of the central gain theory requires that changes in sound-evoked activity be explicitly linked to perceptual alterations of loudness. Here we combined an operant conditioning task that uses a subject's reaction time to auditory stimuli to produce reliable measures of loudness growth with chronic electrophysiological recordings from the auditory cortex and inferior colliculus of awake, behaviorally-phenotyped animals. In this manner, we could directly correlate daily assessments of loudness perception with neurophysiological measures of sound encoding within the same animal. We validated this novel psychophysical-electrophysiological paradigm with a salicylate-induced model of hearing loss and hyperacusis, as high doses of sodium salicylate reliably induce temporary hearing loss, neural hyperactivity, and auditory perceptual disruptions like tinnitus and hyperacusis. Salicylate induced parallel changes to loudness growth and evoked response-intensity functions consistent with temporary hearing loss and hyperacusis. Most importantly, we found that salicylate-mediated changes in loudness growth and sound-evoked activity were correlated within individual animals. These results provide strong support for the central gain model of hyperacusis and demonstrate the utility of using an experimental design that allows for within-subject comparison of behavioral and electrophysiological measures, thereby making inter-subject variability a strength rather than a limitation.